Sfinții Doctori fără de arginți Cosma și Damian sau medicină și credință întrupate - Leb, Ioan-Vasile (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
In the Orthodox Church, the honoring of the Holy Martyrs Cosmas and Damian, who died in Rome, is celebrated on July 1, and those in Asia on November 1. Very well known, the „silverless” holy doctors Cosmas and Damian have been frequently represented since Antiquity, they appear in various images, on seals, on coins, in the decorations of sanctuaries and in iconography. Saints Cosmas and Damian, doctors ”without silver” and patrons of doctors, were and are not only models of doctors and true Christians, but saints who embodied through their activity the two unique missions: medicine and faith, still performing miracles for which Christians sing praises unceasingly. Their only payment was for the healed to believe in Christ, from Whom the healing came.